2007
DOI: 10.1037/0882-7974.22.2.341
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in responses to thoughts of one's own death: Mortality salience and judgments of moral transgressions.

Abstract: Two experiments explored age differences in response to reminders of death. Terror management research has shown that death reminders lead to increased adherence to and defense of one's cultural worldview. In Study 1, the effect of mortality salience (MS) on evaluations of moral transgressions made by younger and older adults was compared. Whereas younger adults showed the typical pattern of harsher judgments in response to MS, older adults did not. Study 2 compared younger and older adults' responses to both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
135
7
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(155 citation statements)
references
References 69 publications
9
135
7
4
Order By: Relevance
“…These studies indicate that older adults, especially in the last stage of life, tend to achieve greater acceptance of the inevitability of their own death. The different reactions of older and younger adults to mortality salience is also reflected in studies that have found that young adults respond to mortality salience induction as predicted according to terror management theory, that is, by holding a harsher judgment of moral transgressions and by engaging in health-promoting behaviours, whereas older adults do not (Bozo et al 2009;Maxfield et al 2007). …”
Section: Ageism Among Older Adults In Light Of Terror Management Theorymentioning
confidence: 97%
“…These studies indicate that older adults, especially in the last stage of life, tend to achieve greater acceptance of the inevitability of their own death. The different reactions of older and younger adults to mortality salience is also reflected in studies that have found that young adults respond to mortality salience induction as predicted according to terror management theory, that is, by holding a harsher judgment of moral transgressions and by engaging in health-promoting behaviours, whereas older adults do not (Bozo et al 2009;Maxfield et al 2007). …”
Section: Ageism Among Older Adults In Light Of Terror Management Theorymentioning
confidence: 97%
“…Yet, whether or not they need to form an estimate depends on how much attention they pay to the respective behavior, which itself is age-dependent. For example, older adults pay more attention to physical symptoms because of an increased salience of their mortality (Maxfield et al 2007). In line with Borchelt et al's (1999) finding that older adults' responses were less affected by experimental variations of response choices when responding on personally relevant information (frequency of physical symptoms), Schmitz et al (2002) found that there was more than 85 % agreement between self-reports and physician reports for the recall of physician visits.…”
Section: Using Response Options To Understand and Interpret Questionsmentioning
confidence: 99%
“…As moral standards constitute an essential part of one's cultural worldview, older adults may adhere more closely to culturally valued moral standards compared to younger adults, thus make harsher judgments about transgressions of those standards. In fact, a study that compared younger and older adults on their moral judgments following the mortality salience manipulation found that the effect of mortality salience in causing a harsher punishment of moral transgression was found only among younger participants-older participants generally suggested a harsher punishment with or without the mortality salience manipulation (Maxfield et al 2007). This pattern suggests that mortality salience may be chronically high among older adults, so they would defend culturally valued moral rules more rigidly compared with younger adults.…”
Section: Age Differences In Moral Judgment Across Lifespanmentioning
confidence: 99%